Everything Under the Heavens : How the Past Helps Shape China's Push for Global Power - French, Howard W. (New York Vintage Books, 2018)
"For many years after its reform and opening in 1978, China maintained an attitude of false modesty about its ambitions. That role, reports Howard French, has been set aside. China has asserted its place among the global heavyweights, revealing its plans for pan-Asian dominance by building its navy, increasing territorial claims to areas like the South China Sea, and diplomatically and economically bullying smaller players. We see how its actions affecting its nearest neighbors -- Japan and Vietnam, among others -- can tell us much of how it will deal with the rest of the world. Underlying this attitude is a strain of thinking that casts China's present-day moves in decidedly historical terms, as the path to restoring the dynastic glory of the past. If we understand how that historical identity relates to current actions, in ways ideological, philosophical, and even legal, we can anticipate just what kind of global power China stands to become--and to interact wisely with a future peer."--Jacket flap.
Include Illustrations, Notes, Maps and Index
Keywords: China -- Asia -- Strategic culture